Safety of paediatric tracheal intubation after non‐invasive ventilation failure. Issue 2 (16th June 2015) - Crulli, Benjamin; Loron, Gauthier; Nishisaki, Akira; Harrington, Karen; Essouri, Sandrine; Emeriaud, Guillaume
SUMMARY: Context: Non‐invasive ventilation (NIV) is increasingly used in pediatric intensive care units to limit the complications associated with intubation. However, NIV may fail, and the delay in initiating invasive ventilation may be associated with adverse outcomes. The objective of this retrospective study was to evaluate the safety of tracheal intubation after NIV failure. Methods: Consecutive tracheal intubation procedures were prospectively evaluated in our PICU from 01/2011 to 02/2012, as part of the National Emergency Airway Registry for Children (NEAR4KIDS) collaborative. The incidence of severe tracheal intubation associated events (TIAEs, including cardiac arrest, esophageal intubation with delayed recognition, emesis with aspiration, hypotension requiring intervention, laryngospasm, malignant hyperthermia, pneumothorax, and pneumomediastinum) and severe desaturation (below 80% when pre‐intubation saturation was greater than 94%) were recorded prospectively. NIV use before intubation was retrospectively assessed. Results: 100 consecutive intubation events were analyzed, 46 of which followed NIV failure. NIV exposed and non‐exposed groups had different baseline characteristics, with lower weight, more frequent lower airway and lung disorder, and lower PIM2 score at admission in NIV failure patients (all P  <0.05). The nasal route for intubation was more frequent in NIV patients ( P  < 0.01). The incidence of severe TIAE or desaturation was 41% in the NIV failure group and 24% in primarily intubated patients ( P  = 0.09). Conclusion: Complications occurred in 41% of intubations after NIV failure in this series. Further research is warranted to evaluate strategies to prevent these complications and to identify conditions in which intubation should not be delayed for a trial of NIV.Pediatr Pulmonol. 2016;51:165–172. © 2015 Wiley Periodicals, Inc.